2018
DOI: 10.1152/japplphysiol.00743.2017
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic PVN contributes to acute intermittent hypoxia-induced sympathetic but not phrenic long-term facilitation

Abstract: Blackburn MB, Andrade MA, Toney GM. Hypothalamic PVN contributes to acute intermittent hypoxia-induced sympathetic but not phrenic long-term facilitation. J Appl Physiol 124: 1233-1243, 2018. First published December 19, 2017; doi: 10.1152/japplphysiol.00743.2017 .- Acute intermittent hypoxia (AIH) repetitively activates the arterial chemoreflex and triggers a progressive increase of sympathetic nerve activity (SNA) and phrenic nerve activity (PNA) referred to as sympathetic and phrenic long-term facilitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…In comparison, after IH exposure, the transcription factor Δ FosB was elevated in the PVN to mediate neuronal activation 8 ; unfortunately, the CeA wasn’t examined in that study. Functional studies have demonstrated that PVN neurons contribute to IH-induced sympathetic activation and hypertension 6,41 . Based on these studies, it is likely that the descending CRH pathway from the PVN to the NTS plays an important role in IH-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, after IH exposure, the transcription factor Δ FosB was elevated in the PVN to mediate neuronal activation 8 ; unfortunately, the CeA wasn’t examined in that study. Functional studies have demonstrated that PVN neurons contribute to IH-induced sympathetic activation and hypertension 6,41 . Based on these studies, it is likely that the descending CRH pathway from the PVN to the NTS plays an important role in IH-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The PVN plays an important role in respiratory modulation and PVN activation increases respiratory frequency and tidal volume (58,196,247). Furthermore, PVN lesion or inhibition blunts responses to cyanide-evoked chemoreceptor activation and intermittent hypoxia (22,156,174). The current data confirm and extend these studies by showing that inhibition of PVN neurons also attenuates the increase in respiratory frequency and tidal volume due to progressive acute hypoxia.…”
Section: Discussionsupporting
confidence: 83%
“…In the face of severe stress, the PVN and VLM are critical areas for mediating the hyperglycemic response ( Zhao et al, 2017 ). Another important area of the hypothalamus for glucose homeostasis is the ventromedial hypothalamus (VMH) which projects to a wide range of sympathetic targets, including the PVN, the VLM and the NTS ( Lindberg et al, 2013 ), which are all involved in the responses to intermittent hypoxia as described above ( Mifflin et al, 2015 ; Shell et al, 2016 ; Blackburn et al, 2018 ; Maruyama et al, 2019 ). While there is no clear evidence of the neurocircuitry involved in the glycemic response to acute IHx, there is substantial knowledge of the effects of GABA on the glucoregulatory neurons in the VMH and the sympathoadrenal glucoregulatory reflex.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic effects of OSA are well accepted, with patients presenting with increased daytime muscle sympathetic activity (Narkiewicz and Somers, 1997). IHx in anesthetized rodent models (Dick et al, 2007;Xing and Pilowsky, 2010;Blackburn et al, 2018;Kakall et al, 2018b;Kim et al, 2018;Roy et al, 2018;Farnham et al, 2019) and conscious humans (Louis and Punjabi, 2009;Gilmartin et al, 2010;Tamisier et al, 2011) also both demonstrate persistent increases in sympathetic nerve activity. In the case of chronic IHx, conscious rodent models develop increases in blood pressure (Sharpe et al, 2013) and glucose dysregulation (Polak et al, 2013;Fu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%